Petrology and geochemistry of the lower group chromitites and host rocks on the farm Zandspruit 168 JP, Western Bushveld Complex - Botha, Michael James (Rhodes University, Faculty of Science, Department of Geology, 1988)
The eight Lower Group chromitite layers of the Ruighoek Pyroxenite in the area west of the Pilanesberg (LGl - LG7), on the farm Zandspruit 168 JP, were sampled in borehole cores drilled through the succession. The stratigraphic succession faIls within Cameron's (980) units B to E of the Critical Zone. The lowermost layer of the Lower Group, the LG 1 chromitite, is located some 440 metres below the MG 2 (Middle Group) chromitite layer, above which the first appearance of cumulus plagioclase in the Complex is seen. By convention, this horizon is designated the top of the Ruighoek Pyroxenite in the Western Bushveld Complex. Homogeneous units of chromite-bearing orthopyroxenite (bronzitite), exhibiting inconspicuous layering defined in terms of variations in orthopyroxene grain-size host all but one of the Lower Group layers; the LG 4 chromitite layer is exposed within an olivine-rich subunit 23 metres in thickness (Câ‚ƒ subunit). The cumulative thickness of chromitite is 2,92 metres or 0,8 per cent of the studied section, which is 381 metres in thickness. Minimum and maximum thicknesses of the LGl - LG7 layers exposed in drill core are 17 and 81 centimetres, respectively, with minor chromitite layers ranging between 2 and 5 centimetres in thickness. Weighted mean Crâ‚‚0â‚ƒ contents of units B to E vary between 1,17 and 3,22 per cent, with the latter estimate representative of the Dâ‚‚ subunit which hosts the LG 6 chromitite layer. The LG 6 is correlated with the Steelpoort layer of the Eastern Bushveld Complex, and varies between 76 and 81 centimetres in thickness under a large portion of the farm Zandspruit. An undisturbed succession striking N15Â°E and dipping 12 - 15Â°E is depicted within the studied area, which is bounded on the eastern side by the north-striking Frank fault. Major folding of the layered succession is evident to the north of the area, where the layering adjacent to the trace of the fault dips 35Â° to the southwest. Particular attention is paid in the present study to (a) the nature of chromitite layers and their host rocks, (b) the contrast between the mineral chemistry of weakly disseminated chromite and grains within massive ore layers, (c) concentrations of Cr, V, Ni, Co, Sc and Ti in orthopyroxene in relation to stratigraphic height, and levels of Sr, Ba and Zr associated with hypothetically pure, intercumulus plagioclase feldspar, and (d) possible mechanisms which induce crystallization of chromitite layers containing 50 per cent Crâ‚‚0â‚ƒ from magma with a Cr content of less than 1 000 ppm. Electron microprobe studies of chromite in relation to mineralogical and textural environment clearly reveal that (a) the proportions of Cr and Al cations are linked to paragenesis: higher Al/Cr ratios characterize olivine-bearing domains, whereas grains intergrown with plagioclase feldspar exhibit low AI/Cr ratios, and (b) Al contents rise with a decline in Mg/(Mg + FeÂ²â º) from high values to a value of 0,450, then decrease with a further decline in Mg/(Mg + FeÂ²â º). The paragenetically later trend is emphasized in a large population of chromite grains which escaped early encapsulation in orthopyroxene crystals and continued to grow in the environment of intercumulus plagioclase. Within-and between-sample compositional variation of grains in silicate-rich domains is modelled in terms of in situ growth increments, diffusive homogenization of zonal structures, and residence time within interstitial melt. Fractionation trends, as measured by Mg/(Mg + FeÂ²â º) ratios in whole-rock and/or microprobe studies of orthopyroxene, are reversed in relation to stratigraphic height towards the top of the B unit and in the overlying C unit. These data are supported, for example, by lower vanadium contents and higher Ni/Sc ratios in hypothetically pure orthopyroxene. Small olivine crystals in chromite-rich domains are enriched in Ni relative to coarse-grained olivine in adjacent dunite: a feature attributed to early isolation of primocrysts from magma in the former case, and in situ equilibration between olivine crystals and Ni-depleted residual melt in the latter case . Similarly, rising Ni contents and Mg/(Mg + FeÂ²â º) ratios of orthopyroxene with increasing stratigraphic height in the footwall of the LG 6 chromitite layer, linked to a progressive decline in orthopyroxene grain-size, are effects which may arise out of early separation of interstitial melt from orthopyroxene cumulates. A model is thus proposed which (a) links the thickness of chromitite layers to the vertical separation between successive layers or the thickness of fine-grained orthopyroxenite in the footwall, (b) ascribes copious nucleation of chromite to liquid mixing of this footwall derived, Cr - depleted contaminant with influxes of hot, primitive magma, and (c) tenders the notion that the present modal proportion of mesostasis in the footwall of a chromitite layer serves as a reciprocal measure of the volume of fractionated exudate
Keywords: Petrology -- Africa, Southern; Geochemistry